Merancang Sistem Informasi Berbasis Web Givan Petshop - Jefri Ramadi; A Walfajri fachriza; Dhifa Arifan Abadi; Rafael Oscar; Yogi Wahyu (Jurnal Vokasi Teknik Informatika, 2025)
The development of digital solutions for small and medium-sized enterprises (SMEs) is essential in supporting operational efficiency and customer engagement. This study presents the design and implementation of the Givan Petshop Information System, a web-based platform developed using a sequential linear methodology. The system aims to centralize and streamline business processes including inventory management, promotional campaigns, grooming service scheduling, and customer interactions. The development process encompassed thorough needs analysis, structured database modeling, and responsive user interface design for both admin and client users. Key features include real-time dashboards, dynamic product and service management, and integrated contact information access. The system was built using Visual Studio Code, MySQL, and XAMPP on a Windows-based environment and tested through interface simulations and functional evaluations. Results indicate that the system effectively supports business administration and improves the accessibility of information for users. While the system functions as intended in the development environment, limitations include the absence of real-user feedback and scalability testing. Future research is recommended to conduct usability testing in real-world settings, integrate mobile and cloud functionalities, and explore smart automation features to further enhance performance.